cDNA cloning of the bovine low density lipoprotein receptor: feedback regulation of a receptor mRNA. - Russell, D W (1983)
The low density lipoprotein (LDL) receptor belongs to a class of migrant cell surface proteins that mediate endocytosis of macromolecular ligands. No cDNAs for this class of proteins have been isolated to date. In the current paper, we report the isolation of a cDNA clone for the LDL receptor from a bovine adrenal cDNA library. The library was constructed by the Okayama-Berg method from poly(A)+ RNA that had been enriched in receptor mRNA by immunopurification of polysomes. Mixtures of synthetic oligonucleotides encoding the amino acid sequence of two neighboring regions of a single cyanogen bromide fragment were used as hybridization probes to identify a recombinant plasmid containing the LDL receptor cDNA. This plasmid, designated pLDLR-1, contains a 2.8-kilobase (kb) insert that includes a sequence which corresponds to the known amino acid sequence of a 36-residue cyanogen bromide fragment of the receptor. pLDLR-1 hybridized to a mRNA of approximately equal to 5.5 kb in the bovine adrenal gland. This mRNA, like the receptor protein, was 9-fold more abundant in bovine adrenal than in bovine liver. pLDLR-1 cross-hybridized to a mRNA of approximately equal to 5.5 kb in cultured human epidermoid carcinoma A-431 cells. This mRNA was markedly reduced in amount when sterols were added to the culture medium, an observation that explains the previously observed feedback regulation of LDL receptor protein. Southern blot analysis of bovine genomic DNA with 32P-labeled pLDLR-1 revealed a simple pattern of hybridization, consistent with a single-copy gene containing introns.